Water Issues in Himalayan South Asia
XX, 209 p. 8 illus., 3 illus. in color.
Keywords: The book looks into the domestic water issues and disputes in the Himalayan South Asian countries, and based on it analyzes trans-boundary water disputes. Himalayan South Asia comprises India, Pakistan, Bangladesh, Nepal, Bhutan, and Afghanistan. All except Afghanistan share river waters with India. Home to some of the major river basins of the world, a part of this region falls into water scarce zone, and according to the United Nations Water Report of 2018 some of them will experience severe water scarcity by 2050. The book also studies water issues in China. Though the country is not a part of the Himalayan South Asia, most of the major rivers of this region originate in China. Over the years, China has been alleged by countries like India for diverting, choking or using the trans-boundary river waters for its purpose. Understanding water competition and issues in China will help one to understand its transboundary water behavior.